Medical Image Encryption through Chaotic Asymmetric Cryptosystem - K. Mehar Roshini,; Dr.K. Venkataramana, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
With the soaring heights of digital advancements, the necessity of securing medical images has become utmost, as healthcare information remains highly confidential. The proposed work being presented suggests a new approach for image encryption which is based on Elliptic Curve Cryptography and on Blum-Goldwasser Cryptosystem in a public-key environment beside the generation of chaotic sequence to increase the randomness of the system. The encryption workflow begins with secure key exchange, using the computational efficiency of ECC in conjunction with the probabilistic security features of BGC, which are based on the discrete logarithm and quadratic residuosity problems, to initiate the encryption process. Chaotic map pixel randomization is added to obscure data even further by introducing high unpredictability and resistance against pattern-based attacks. The added security layers are the combination of ECC and BGC, which make the system robust against brute-force attempts and differential cryptanalysis. In-depth performance evaluations through extensive simulation narratively support the superiority of the proposed method over existing cryptosystems. Telemetry Evidence-It achieved the highest information entropy of 7.9998, which indicates nearly maximum randomness; An average correlation coefficient of 0.0010 implies negligible pixel dependency while an NPCR of 99.6901% and UACI of 33.5260% therefore indicate utmost resistance towards differential attacks. Moreover, the encryption process proceeds in just 0.142 seconds, thereby cementing its real-time application feasibility. The proposed hybrid chaotic image encryption method has been substantiated by several experiments as showing much strength concerning emergent cyber threats against medical data and other sensitive images.
Keywords: Blum-Goldwasser Cryptosystem; Chaotic Encryption; Alexander Raharjo; Elliptic Curve Cryptography; Image Encryption; Public Key Encryption